TIGERNUT: A NUTRIENT-RICH UNDERUTILIZED CROP WITH MANY POTENTIALS - Abdullahi, N.; Badau, Mamudu Halidu; Umar, Nasiru Bilkisu; Yunusa, ALkasim Kabiru; Rilwan , Abdulrashid; Jibril, Hassana; Iliyasu, Raliya (FUDMA JOURNAL OF SCIENCES, 2022)
There is a need to explore the nutritional and medicinal potentials of underutilized crops such as tigernut. Most conventional foods that are rich and balanced are scarce and expensive, and cannot be afforded by consumers in developing countries. Promoting tigernut consumption will play an imperative role in the health, nutrition, and economy of many developing countries. This review was intended to provide an overview on the nutritional and nutraceutical properties of various tigernut products. Also to provide information on the effects of various processing operations on the nutritional and functional properties of various tigernut products. Tigernut is rich in essential nutrients, numerous bioactive compounds with proven health benefits were found in all tigernut cultivars. Genetic variations, environmental and growing conditions make the yellow, brown, and black cultivars of tigernut to have different physicochemical, phytochemicals and functional properties. Tigernut and its products are recommended in the production of bakery goods and complementary foods. Tigernut extracts are potential candidates for the production of nutraceutical diets and drugs. Compounds with anti-inflammatory, antioxidant, anticancer, antidiabetic, antihypertensive, anti-obesity, antimicrobial and antiseptic properties were found in tigernut. The oil can be used in cooking and frying, the oil is rich in polyunsaturated fatty acids, phytosterols, and tocopherols. The fatty acids composition of the oil is affected by the extraction methods. In addition to industrial applications, wastes and by-products from tigernut processing can also be used as food and feed ingredients.
Keywords: Functional food, nutraceutical, tigernut flour tigernut milk, tigernut oil